Faktor-faktor yang mempengaruhi akuntabilitas pengelolaan dana desa - Fahera, Gangga Izza; Satyawan, Made Dudy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The research was conducted with the intention of empirically testing the influence of the competence of the village apparatus, the utilization of the village financial system, community participation, and the government's internal control system on the accountability of village fund management in Kepohbaru District, Bojonegoro Regency. This research uses quantitative methods. The data used is primary data obtained from questionnaires that have been distributed. The purposive sampling technique was used in this study and obtained 102 respondents consisting of village heads, village secretaries, heads of financial affairs, heads of general affairs, government kasi, people's welfare kasi, service kasi, planning kasi and hamlet heads in Kepobharu District, Bojonegoro Regency. After testing, results were obtained, namely internal government control, the competence of village apparatus, and community participation had a significant effect on the accountability of village fund management, while the use of siskeudes did not affect the accountability of village fund management.